Towards low loss non-volatile phase change materials in mid index waveguides - Joaquin Faneca; Ioannis Zeimpekis; S T Ilie; Thalía Domínguez Bucio; Katarzyna Grabska; Daniel W Hewak; Frederic Y Gardes (Neuromorphic Computing and Engineering, 2021)
Photonic integrated circuits currently use platform intrinsic thermo-optic and electro-optic effects to implement dynamic functions such as switching, modulation and other processing. Currently, there is a drive to implement field programmable photonic circuits, a need which is only magnified by new neuromorphic and quantum computing applications. The most promising non-volatile photonic components employ phase change materials such as GST and GSST, which had their origin in electronic memory. However, in the optical domain, these compounds introduce significant losses potentially preventing a large number of applications. Here, we evaluate the use of two newly introduced low loss phase change materials, Sb _2 S _3 and Sb _2 Se _3 , on a silicon nitride photonic platform for future implementation in neuromorphic computing. We focus the study on Mach–Zehnder interferometers that operate at the O and C bands to demonstrate the performance of the system. Our measurements show an insertion loss below 0.04 dB μm ^−1 for Sb _2 S _3 and lower than 0.09 dB μm ^−1 for Sb _2 Se _3 cladded devices for both amorphous and crystalline phases. The effective refractive index contrast for Sb _2 S _3 on SiNx was measured to be 0.05 at 1310 nm and 0.02 at 1550 nm, whereas for Sb _2 Se _3 , it was 0.03 at 1310 nm and 0.05 at 1550 nm highlighting the performance of the integrated device.